Early surgery or conservative management for asymptomatic severe aortic stenosis: Meta‐analysis of RECOVERY and AVATAR. Issue 12 (6th November 2022) - Changal, Khalid; Devarasetty, Pratyush Pavan; Royfman, Rachel; Veria, Spiro; Yassen, Mohammad; Vyas, Rohit; Gössl, Mario
Abstract: The standard practice for management for asymptomatic severe aortic stenosis with a normal left ventricular systolic function is conservative management with a few exceptions. This practice is challenged by two recent randomized controlled trials (RCT). All the prior data is observational. We performed a meta‐analysis of these 2 RCTs to determine if early surgical aortic valve replacement in this patient population is beneficial compared with the standard conservative therapy.